Developing aspects of sociolinguistic competence: focus on pre-school learners - Potočková, Michaela (Univerzita Pardubice, 2021)
This thesis deals with the development of sociolinguistic competence within pre-school children in the English language. The theoretical section first defines the characteristics of the pre-school child, the characteristics of the teacher, the principles and teaching techniques for the pre-school pupils, but also sociolinguistic competence and its development. The first part of this Bachelor thesis serves as a basis for the elaboration of the practical part, where are gradually presented six lesson plans, which helps to develop precisely sociolinguistic competence in pre-school children in the English language.
Rozvoj aspektů sociolingvistické kompetence u dětí předškolního věku
Keywords: sociolingvistická kompetence; předškolní žáci; výuka anglického jazyka; plánování hodin; sociolinguistic competence; pre-school learners; English language teaching; lesson planning